Social network dynamics precede a mass eviction in group-living rhesus macaques. (February 2018) - Larson, Sam M.; Ruiz-Lambides, Angelina; Platt, Michael L.; Brent, Lauren J.N.
Abstract : Network dynamics can reveal information about the adaptive function of social behaviour and the extent to which social relationships can flexibly respond to extrinsic pressures. Changes in social networks occur following changes to the social and physical environment. By contrast, we have limited understanding of whether changes in social networks precede major group events. Permanent evictions can be important determinants of gene flow and population structure and are a clear example of an event that might be preceded by social network dynamics. Here we examined the social networks of a group of rhesus macaques, Macaca mulatta, in the 2 years leading up to the eviction of 22% of adult females, which are the philopatric sex. We found that females engaged in the same amount of aggression and grooming in the 2 years leading up to the eviction but that there were clear changes in their choice of social partners. Females that would eventually be evicted received more aggression from lower-ranking females as the eviction approached. Evicted females also became more discriminating in their grooming relationships in the year nearer the split, showing a greater preference for one another and becoming more cliquish. Put simply, the females that would later be evicted continued to travel with the rest of the group as the eviction approached but were less likely to interact with other group members in an affiliative manner. These results have potential implications for understanding group cohesion and the balance between cooperation and competition that mediates social groups. Highlights: Network dynamics have the power to reveal the function of social behaviours. We explored network dynamics leading up to the fissioning of a social group. Females that would be evicted became less likely to interact with others. Network changes were subtle and revealed only through analysis. Our results align with the idea that social bonds contribute to group cohesion.